The mechanics of web handling - Roisum, David R (TAPPI Press, 1998)
This unique book covers many aspects of web handling for manufacturing, converting, and printing. The book is applicable to any web including paper, film, foil, nonwovens, and textiles. This book is designed for product, process, and maintenance engineers responsible for web machinery. Through this valuable text, readers will understand better how to design and operate machinery to avoid wrinkles, web breaks, registration, guiding, and other types of costly web problems.